(untitled) (Tempo e Argumento, 2012)
The present article presents a brief historical analysis about the private military companies and its progressive presence in military interventions promoted by the United States of America since the end of Cold War. Departing from a specific point, the period of “War on Terror” promoted by Bush government, the present study proposes a preliminary analysis about the main military companies in the field today, the regulatory limits of private military companies, the interests behind the growing use of this type of private service and the challenges for the comprehension of this phenomenon in the framing of the military issues in the 21 st century.